The effects of honey on postmenopausal women - Yaacob, Lili Husniati (2010)
Results of recent trial have shown some negative effects of hormone replacement therapy on postmenopausal women. Therefore there has been a move towards using alternative medicine as Objectives: To investigate the effects of Tualang Honey on the safety profiles, cardiovascular risk factors, changes in hormones and also bone density in postmenopausal women. Methods: A randomized, controlled trial comparing the effects of Tualang Honey 20 gm/day for a 4-month intervention period among healthy post-menopausal Malay women aged 45-60 years old was conducted. The primary outcome measures were to evaluate changes from baseline on the safety profiles, cardiovascular risk factors, hormonal profiles and bone loss of Tualang honey as compared to hormone replacement therapy. Paired t-test was used to analyze the difference between the outcome at baseline and 4 months of intervention in both groups. Analysis of covariance (ANCOVA) was performed to evaluate the difference between groups at the study end-point with baseline scores as co-variates. xiii a treatment for menopausal problems and honey is one of the alternative. Results: Fourty and thirty nine women were randomly assigned to Tualang Honey and hormone replacement therapy group respectively with no statistical difference in socio demographic, anthropometries and duration of menopause. There were no difference in the bone densitometry at the end of the four month in both groups. There were also no significant changes in safety parameters seen in the haematological profile, liver enzymes and renal function in the two randomized groups. However, there was a significant increase in the total cholesterol, LDL-C and FBS in the honey treated group compared from baseline. There was improvement of FSFI, LH and estradiol levels in the HRT group. There were 35.4% of participants who reported per vaginal bleeding, where all of them were from the hormone treated group Conclusion: Daily intake of Honey at 20 mg/day for four month was found to be safe to use and have the same effect on bone densitometry compared with hormone replacement therapy. However consumption of honey for four months was associated with an increase in the cholesterol and fasting blood sugar level.